Use of Elastic Stain Technique to Detect Histologically Occult Vascular Invasion in Resected Colorectal Carcinomas at Danbury Hospital. (28th October 2021) - Karki, S; Steven, S; Kaur, G; Das, D; Agarwal, R
Abstract: Introduction/Objective: Colorectal carcinoma (CRC) represents a leading cause of cancer related death in the western world and is by far the most common malignancy of the gastrointestinal tract. Vascular invasion (VI), in particular extramural VI by tumor is recognized as a feature of colorectal cancer progression, and the latter is an independent prognostic indicator of disease recurrence and survival in colorectal carcinoma. The purpose of this study is to detect VI in resected colorectal tumor samples and compare sensitivity of elastic staining to routine H&E staining at Danbury Hospital. Methods/Case Report: A total of 50 colorectal cancer specimens from segmental colon resection or endoscopic polypectomy performed at Danbury Hospital over a 3-year period were included. Histologic sections of each tumor were assessed for the presence of VI by routine H&E staining. Superficial recuts of each tumor were subjected to elastic Von Giesen staining and reassessed for the presence of vascular invasion. Sensitivity of routine H&E staining for the detection of VI was calculated with elastic stain serving as the "gold standard". Results (if a Case Study enter NA): In this study, VI by carcinoma was identified by H&E stain and/or elastic stain in 17 (34%) out of 50 cases. H&E stain and elastic stain detected VI in 12 (24%) and 16 (32%) out of 50 cases, respectively. There was a single case for which H&E stain showed vascular invasion that was not confirmed by elastic stain, representing a false negative for the H&E technique. Elastic staining detected VI in 5 cases for which the corresponding H&E stain was falsely negative for VI. Overall, vascular invasion status (absent or present) was concordant in 44 (88 %) of the 50 cases. With elastic stain deemed the "gold standard" for VI detection, the sensitivity, specificity, negative predictive value, and positive predictive value of H&E stain were found to be 68.7%, 97.0%, 86.8%, and 91.6%, respectively. Conclusion: Although H & E staining of colorectal carcinoma tissue sections have a very good specificity and positive predictive value for the detection of VI, this technique suffers from a suboptimal sensitivity. For these reasons, we agree with previously published literature reports that the use of elastic stain as a supplement to H & E staining should be strongly considered for the proper evaluation and prognostication of colorectal carcinoma specimens.